Semiconductor nanoparticle, method for producing the same, and light-emitting device
Patent Information
- Application Number
- JP2024204609
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2017-02-28
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2038-02-15
AI Technical Summary
【0009】 本発明の一態様によれば、バンド端発光を示し、短波長の発光ピーク波長を有する半導体ナノ粒子を提供することができる。
Smart Images

Figure 2025032151000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to semiconductor nanoparticles, a method for producing the same, and a light-emitting device. [Background technology]
[0002] It is known that semiconductor particles exhibit a quantum size effect when their particle size is, for example, 10 nm or less, and such nanoparticles are called quantum dots (also called semiconductor quantum dots). The quantum size effect refers to the phenomenon in which the valence band and conduction band, which are considered continuous in bulk particles, become discrete in nanoparticles, and the band gap energy changes depending on the particle size.
[0003] Since quantum dots can absorb light and convert the wavelength of light to light corresponding to the band gap energy, white light emitting devices utilizing quantum dot emission have been proposed (see, for example, Patent Documents 1 and 2). Specifically, it has been proposed to absorb a part of the light emitted from a light emitting diode (LED) chip into quantum dots to obtain white light as a mixture of the light emitted from the quantum dots and the light emitted from the LED chip. These patent documents propose the use of binary quantum dots of groups 12-16 such as CdSe and CdTe, and groups 14-16 such as PbS and PbSe. In addition, tellurium compound nanoparticles (see, for example, Patent Document 3) and sulfide nanoparticles (see, for example, Patent Document 4) have been considered as ternary semiconductor nanoparticles capable of band edge emission and having a low toxicity composition. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2012-212862 A [Patent Document 2] JP 2010-177656 A [Patent Document 3] JP 2017-014476 A [Patent Document 4] JP 2017-025201 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, the semiconductor nanoparticles described in Patent Documents 3 and 4 have an emission peak wavelength in a relatively long wavelength region. Therefore, an object of one aspect of the present invention is to provide semiconductor nanoparticles that exhibit band edge emission and have an emission peak wavelength in a short wavelength region. [Means for solving the problem]
[0006] The first aspect is semiconductor nanoparticles which contain Ag, In, Ga, and S, in which the ratio of the number of Ga atoms to the total number of In and Ga atoms is 0.95 or less, which emit light when irradiated with light having an emission peak wavelength in the range of 500 nm or more and less than 590 nm, and whose half-width of the emission peak is 70 nm or less, and which have an average particle size of 10 nm or less.
[0007] A second aspect is a method for producing semiconductor nanoparticles comprising providing a mixture comprising silver acetate, indium acetylacetonate, gallium acetylacetonate, a sulfur source, and an organic solvent, and heat treating the mixture.
[0008] A third aspect is a light-emitting device comprising a light conversion member containing the semiconductor nanoparticles and a semiconductor light-emitting element. Effect of the Invention
[0009] According to one aspect of the present invention, it is possible to provide semiconductor nanoparticles that exhibit band edge emission and have a short emission peak wavelength. [Brief description of the drawings]
[0010] [Figure 1] FIG. 2 shows the emission spectrum of semiconductor nanoparticles. [Diagram 2] FIG. 2 is a diagram showing the absorption spectrum of semiconductor nanoparticles. [Diagram 3] 1 shows an XRD pattern of semiconductor nanoparticles according to Example 4. [Figure 4] FIG. 2 shows the emission spectrum of semiconductor nanoparticles. [Diagram 5] FIG. 2 is a diagram showing the absorption spectrum of semiconductor nanoparticles. [Figure 6] FIG. 1 shows the emission spectra of the core-shell semiconductor nanoparticles according to Examples 12 to 16. [Figure 7] FIG. 1 shows the emission spectra of the core-shell semiconductor nanoparticles according to Examples 17 and 18. [Figure 8] FIG. 13 shows the emission spectrum of the TOP-modified core-shell semiconductor nanoparticles of Example 19. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The embodiments will be described in detail below. However, the embodiments shown below are examples of semiconductor nanoparticles and their manufacturing method and light-emitting device for embodying the technical idea of the present invention, and the present invention is not limited to the semiconductor nanoparticles and their manufacturing method and light-emitting device shown below. In addition, in this specification, the term "process" includes not only an independent process, but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process is achieved. When a plurality of substances corresponding to each component are present in the composition, the content of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified.
[0012] Semiconductor Nanoparticles The semiconductor nanoparticles according to the first embodiment contain silver (Ag), indium (In), gallium (Ga) and sulfur (S). The semiconductor nanoparticles have a ratio of the number of Ga atoms to the total number of In and Ga atoms (Ga / (Ga+In)) of 0.95 or less. The semiconductor nanoparticles emit light when irradiated with light, with an emission peak wavelength in the range of 500 nm or more and less than 590 nm, and the half-width of the emission peak in the emission spectrum is 70 nm or less. The semiconductor nanoparticles also have an average particle size of 10 nm or less.
[0013] The semiconductor nanoparticles contain Ag, In, Ga, and S, and the ratio of the number of Ga atoms to the total number of In and Ga atoms is within a predetermined range, so that the semiconductor nanoparticles can emit band edge light with an emission peak wavelength that is longer than the wavelength of the excitation light and in the visible region, that is, in the range of 500 nm or more and less than 590 nm.
[0014] The crystal structure of the semiconductor nanoparticles can be at least one selected from the group consisting of tetragonal, hexagonal, and orthorhombic. Semiconductor nanoparticles containing Ag, In, and S and having a tetragonal, hexagonal, or orthorhombic crystal structure are generally introduced in literature as being represented by the composition formula AgInS2. The semiconductor nanoparticles according to this embodiment can be considered to be, for example, a group 13 element, with Ga substituted for a part of In. That is, the composition of the semiconductor nanoparticles is represented, for example, by Ag-In-Ga-S or Ag(In,Ga)S2.
[0015] In addition, among semiconductor nanoparticles represented by a composition formula such as Ag-In-Ga-S, those having a hexagonal crystal structure are wurtzite type, and those having a tetragonal crystal structure are chalcopyrite type. The crystal structure is identified, for example, by measuring an XRD pattern obtained by X-ray diffraction (XRD) analysis. Specifically, the XRD pattern obtained from the semiconductor nanoparticles is compared with a known XRD pattern of a semiconductor nanoparticle represented by a composition of AgInS2, or an XRD pattern obtained by performing a simulation from crystal structure parameters. If any of the known patterns and the simulated patterns match the pattern of the semiconductor nanoparticles, the crystal structure of the semiconductor nanoparticles can be said to be the crystal structure of the matching known or simulated pattern.
[0016] In an aggregate of semiconductor nanoparticles, semiconductor nanoparticles of different crystal structures may be present together, in which case peaks derived from a plurality of crystal structures will be observed in the XRD pattern.
[0017] The semiconductor nanoparticles may be substantially composed of only Ag, In, Ga, and S. Here, the term "substantially" is used in consideration of the fact that elements other than Ag, In, Ga, and S are inevitably included due to the inclusion of impurities, etc.
[0018] The ratio of the number of Ga atoms to the total number of In and Ga atoms, Ga / (Ga+In) (hereinafter also referred to as the "Ga ratio"), can be 0.95 or less, and more preferably 0.2 or more and 0.9 or less.
[0019] The ratio Ag / (Ag+In+Ga) (hereinafter also referred to as "Ag ratio") of the number of Ag atoms to the total number of Ag, In, and Ga atoms can be set to 0.05 or more and 0.55 or less.
[0020] The Ag ratio can be 0.3 or more and 0.55 or less, and the Ga ratio can be 0.5 or more and 0.9 or less, and preferably, the Ag ratio can be 0.35 or more and 0.53 or less, and the Ga ratio can be 0.52 or more and 0.86 or less.
[0021] The Ga ratio can be 0.2 or more and 0.9 or less, and the value of Ga ratio + 2 × Ag ratio can be 1.2 or more and 1.7 or less, and preferably, the Ga ratio can be 0.2 or more and 0.9 or less, the Ag ratio can be 0.3 or more and 0.55 or less, and the value of Ga ratio + 2 × Ag ratio can be 1.2 or more and 1.7 or less.
[0022] The Ag ratio may be 0.05 or more and 0.27 or less, and the Ga ratio may be 0.25 or more and 0.75 or less. Preferably, the Ag ratio may be 0.06 or more and 0.27 or less, and the Ga ratio may be 0.26 or more and 0.73 or less.
[0023] The Ga ratio is 0.2 or more and 0.8 or less, and the value of Ga ratio + 2 × Ag ratio can be 0.6 or more and 1 or less, and preferably, the Ga ratio is 0.2 or more and 0.8 or less, the Ag ratio is 0.05 or more and 0.4 or less, and the value of Ga ratio + 2 × Ag ratio can be 0.6 or more and 1 or less.
[0024] The ratio S / (Ag+In+Ga) of the number of S atoms to the total number of Ag, In, and Ga atoms (hereinafter also referred to as "S ratio") can be, for example, 0.6 or more and 1.6 or less.
[0025] The chemical composition of the semiconductor nanoparticles can be identified, for example, by X-ray fluorescence analysis (XRF). The Ga ratio calculated by Ga / (Ga+In), the Ag ratio calculated by Ag / (Ag+In+Ga), and the S ratio calculated by S / (Ag+In+Ga) are calculated based on the chemical composition measured by this method.
[0026] The semiconductor nanoparticles have an average particle size of 10 nm or less. The average particle size can be, for example, less than 10 nm, preferably 5 nm or less. If the average particle size exceeds 10 nm, it becomes difficult to obtain the quantum size effect and band edge emission. The lower limit of the average particle size is, for example, 1 nm.
[0027] The particle size of semiconductor nanoparticles can be determined, for example, from a TEM image taken using a transmission electron microscope (TEM). Specifically, the length of the longest line segment among those that connect any two points on the periphery of a particle observed in a TEM image and that pass through the inside of the particle is defined as the particle size of the particle.
[0028] However, when the particle has a rod shape, the length of the short axis is regarded as the particle size. Here, a rod-shaped particle refers to a particle having a short axis and a long axis perpendicular to the short axis in a TEM image, and the ratio of the length of the long axis to the length of the short axis is greater than 1.2. A rod-shaped particle is observed in a TEM image, for example, as a quadrangle including a rectangular shape, an ellipse, or a polygon. The shape of the cross section, which is a surface perpendicular to the long axis of the rod shape, may be, for example, a circle, an ellipse, or a polygon. Specifically, for a particle having a rod-like shape, the length of the long axis refers to the length of the longest line segment among the line segments connecting any two points on the periphery of the particle in the case of an ellipse, and refers to the length of the longest line segment among the line segments that are parallel to the longest side that defines the periphery and connect any two points on the periphery of the particle in the case of a rectangular or polygonal shape. The length of the short axis refers to the length of the line segment that is perpendicular to the line segment that defines the length of the longest side among the line segments connecting any two points on the periphery.
[0029] The average particle size of semiconductor nanoparticles is determined by measuring the particle size of all measurable particles observed in a TEM image at a magnification of 50,000 times or more and 150,000 times or less, and calculating the arithmetic average of the particle sizes. Here, a "measurable" particle is one whose entirety can be observed in a TEM image. Therefore, a particle that is "cut off" because a part of it is not included in the imaging range in a TEM image is not measurable. If the number of measurable particles contained in one TEM image is 100 or more, the average particle size is determined using that TEM image. On the other hand, if the number of measurable particles contained in one TEM image is less than 100, the imaging location is changed, another TEM image is obtained, and the particle sizes of 100 or more measurable particles contained in two or more TEM images are measured to determine the average particle size.
[0030] The semiconductor nanoparticles contain Ag, In, Ga, and S, and the ratio of the number of Ga atoms to the total number of In and Ga atoms is within a predetermined range, so that band edge emission is possible. The semiconductor nanoparticles emit light with an emission peak wavelength in the range of 500 nm to less than 590 nm by irradiating light having a peak near 365 nm. The emission peak wavelength can be, for example, 500 nm to 580 nm, 500 nm to 575 nm, and 505 nm to less than 575. It can also be 570 nm to 585 nm, or 575 nm to 580 nm. The half width of the emission peak in the emission spectrum can be, for example, 70 nm or less, 60 nm or less, 55 nm or less, or 50 nm or less. The lower limit of the half width can be, for example, 10 nm or more or 20 nm or more.
[0031] The semiconductor nanoparticles may give other luminescence, such as defect luminescence, in addition to the band edge luminescence. The defect luminescence generally has a long luminescence lifetime and a broad spectrum, with its peak at a longer wavelength side than the band edge luminescence. When both the band edge luminescence and the defect luminescence are obtained, it is preferable that the intensity of the band edge luminescence is greater than that of the defect luminescence.
[0032] The peak position of the band edge emission of semiconductor nanoparticles can be changed by changing the shape and / or average particle size of the semiconductor nanoparticles, particularly the average particle size. For example, if the average particle size of the semiconductor nanoparticles is made smaller, the band gap energy becomes larger due to the quantum size effect, and the peak wavelength of the band edge emission can be shifted to the shorter wavelength side.
[0033] In addition, the peak position of the band edge emission of semiconductor nanoparticles can be changed by changing the composition of the semiconductor nanoparticles. For example, the peak wavelength of the band edge emission can be shifted to the shorter wavelength side by increasing the Ga ratio.
[0034] The semiconductor nanoparticles preferably have an absorption spectrum that shows an exciton peak. The exciton peak is a peak obtained by exciton generation, and the fact that it appears in the absorption spectrum means that the particle size distribution is small and the particles are suitable for band edge emission with few crystal defects. The steeper the exciton peak, the more particles with uniform particle size and few crystal defects are contained in the semiconductor nanoparticle aggregate, so the half width of the emission becomes narrower and the emission efficiency is expected to improve. In the absorption spectrum of the semiconductor nanoparticles of this embodiment, the exciton peak is observed, for example, in the range of 450 nm or more and less than 590 nm.
[0035] The surface of the semiconductor nanoparticles may be modified with a surface modifier, for example, to stabilize the semiconductor nanoparticles and prevent particle aggregation or growth, and / or to improve the dispersibility of the particles in a solvent.
[0036] Examples of the surface modifier include nitrogen-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms, sulfur-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms, and oxygen-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms. Examples of the hydrocarbon group with 4 to 20 carbon atoms include saturated aliphatic hydrocarbon groups such as n-butyl, isobutyl, n-pentyl, n-hexyl, octyl, decyl, dodecyl, hexadecyl, and octadecyl groups; unsaturated aliphatic hydrocarbon groups such as oleyl; alicyclic hydrocarbon groups such as cyclopentyl and cyclohexyl; and aromatic hydrocarbon groups such as phenyl, benzyl, naphthyl, and naphthylmethyl groups. Among these, saturated aliphatic hydrocarbon groups and unsaturated aliphatic hydrocarbon groups are preferred. Examples of the nitrogen-containing compounds include amines and amides, examples of the sulfur-containing compounds include thiols, and examples of the oxygen-containing compounds include fatty acids.
[0037] The surface modifier is preferably a nitrogen-containing compound having a hydrocarbon group having from 4 to 20 carbon atoms. Examples of such nitrogen-containing compounds include alkylamines such as n-butylamine, isobutylamine, n-pentylamine, n-hexylamine, octylamine, decylamine, dodecylamine, hexadecylamine, and octadecylamine, and alkenylamines such as oleylamine.
[0038] Also preferred as the surface modifier is a sulfur-containing compound having a hydrocarbon group having from 4 to 20 carbon atoms. Examples of such sulfur-containing compounds include alkyl thiols such as n-butanethiol, isobutanethiol, n-pentanethiol, n-hexanethiol, octanethiol, decanethiol, dodecanethiol, hexadecanethiol, and octadecanethiol.
[0039] The surface modifier may be used in combination of two or more different compounds. For example, one compound selected from the nitrogen-containing compounds exemplified above (e.g., oleylamine) and one compound selected from the sulfur-containing compounds exemplified above (e.g., dodecanethiol) may be used in combination.
[0040] Method for producing semiconductor nanoparticles The method for producing semiconductor nanoparticles according to the second embodiment includes preparing a mixture containing a silver salt, an indium salt, a gallium salt, a sulfur source, and an organic solvent, and heat-treating the prepared mixture. The mixture preferably contains silver acetate, indium acetylacetonate, gallium acetylacetonate, sulfur or thiourea as a sulfur source, and an organic solvent.
[0041] The mixture can be prepared by adding a silver salt, an indium salt, a gallium salt, and a sulfur source to an organic solvent and mixing them. The content ratios of Ag, In, Ga, and S in the mixture are appropriately selected according to the target composition. For example, the molar ratio of Ga to the total molar amount of In and Ga is 0.2 or more and 0.9 or less. For example, the molar ratio of Ag to the total molar amount of Ag, In, and Ga is 0.05 or more and 0.55 or less. For example, the molar ratio of S to the total molar amount of Ag, In, and Ga is 0.6 or more and 1.6 or less.
[0042] The organic solvent may be an amine having a hydrocarbon group having 4 to 20 carbon atoms, particularly an alkylamine or alkenylamine having 4 to 20 carbon atoms, a thiol having a hydrocarbon group having 4 to 20 carbon atoms, particularly an alkylthiol or alkenylthiol having 4 to 20 carbon atoms, or a phosphine having a hydrocarbon group having 4 to 20 carbon atoms, particularly an alkylphosphine or alkenylphosphine having 4 to 20 carbon atoms. These organic solvents may ultimately be used to modify the surface of the semiconductor nanoparticles obtained. Two or more of these organic solvents may be used in combination, and in particular, a mixed solvent may be used that combines at least one selected from thiols having a hydrocarbon group having 4 to 20 carbon atoms and at least one selected from amines having a hydrocarbon group having 4 to 20 carbon atoms. These organic solvents may also be used in combination with other organic solvents.
[0043] In the method for producing semiconductor nanoparticles, the mixture is heat-treated to generate semiconductor nanoparticles in an organic solvent. The temperature of the heat treatment of the mixture is, for example, 230°C or more and 310°C or less, preferably higher than 260°C and 310°C or less, more preferably 290°C or more and 310°C or less. The heat treatment time is, for example, 5 minutes or more and 20 minutes or less, preferably 5 minutes or more and 15 minutes or less. The heat treatment of the mixture may be performed at two or more temperatures. For example, the mixture may be heated at a temperature of 30°C or more and 155°C or less for 1 minute or more and 15 minutes or less, and then heated at a temperature of 230°C or more and 310°C or less for 5 minutes or more and 20 minutes or less.
[0044] The heat treatment is preferably performed in an inert atmosphere, particularly an argon or nitrogen atmosphere, which can reduce or prevent the production of oxide by-products and the oxidation of the surfaces of the semiconductor nanoparticles.
[0045] After the production of the semiconductor nanoparticles is completed, the obtained semiconductor nanoparticles may be separated from the organic solvent after the treatment, and may be further purified as necessary. The separation is performed, for example, by centrifuging the organic solvent containing the nanoparticles after the production is completed, and taking out the supernatant containing the nanoparticles. The purification can be performed, for example, by adding an organic solvent to the supernatant and centrifuging it, and taking out the semiconductor nanoparticles as a precipitate. The supernatant can also be taken out by volatilizing it. The taken out precipitate may be dried, for example, by vacuum degassing, natural drying, or a combination of vacuum degassing and natural drying. Natural drying may be performed, for example, by leaving it in the air at room temperature and normal pressure, and in that case, it may be left for 20 hours or more, for example, about 30 hours.
[0046] Alternatively, the precipitate taken out may be dispersed in an organic solvent. Purification (addition of alcohol and centrifugation) may be carried out multiple times as necessary. As the alcohol used for purification, a lower alcohol having 1 to 4 carbon atoms, such as methanol, ethanol, or n-propyl alcohol, may be used. When the precipitate is dispersed in an organic solvent, as the organic solvent, a halogen-based solvent, such as chloroform, or a hydrocarbon-based solvent, such as toluene, cyclohexane, hexane, pentane, or octane, may be used.
[0047] Core-shell type semiconductor nanoparticles The semiconductor nanoparticles can be core-shell type semiconductor nanoparticles having a core made of at least one of the semiconductor nanoparticles according to the first embodiment and the semiconductor nanoparticles obtained by the manufacturing method according to the second embodiment, and a shell having a larger band gap energy than the core and forming a heterojunction with the core. The semiconductor nanoparticles can exhibit stronger band edge emission by having a core-shell structure.
[0048] The shell is preferably a semiconductor material consisting essentially of elements from Groups 13 and 16. The elements from Group 13 include B, Al, Ga, In, and Tl, and the elements from Group 16 include O, S, Se, Te, and Po.
[0049] The shell may also be a semiconductor material substantially composed of Group 1, Group 13 and Group 16 elements. By including a Group 1 element in addition to Group 13 and Group 16 elements, defect emission tends to be suppressed. Examples of Group 1 elements include Li, Na, K, Rb and Cs, with Li being preferred because its ionic radius is close to that of Ag.
[0050] The band gap energy of the semiconductor constituting the core varies depending on its composition, but ternary semiconductors of Group 11-Group 13-Group 16 elements generally have a band gap energy of 1.0 eV or more and 3.5 eV or less, and in particular, semiconductors composed of Ag-In-Ga-S have a band gap energy of 2.0 eV or more and 2.5 eV or less, and therefore the composition of the shell may be selected and configured according to the band gap energy of the semiconductor constituting the core. Alternatively, if the composition of the shell is determined in advance, the core may be designed so that the band gap energy of the semiconductor constituting the core is smaller than that of the shell.
[0051] Specifically, the shell can have a band gap energy of, for example, 2.0 eV to 5.0 eV, particularly 2.5 eV to 5.0 eV. The band gap energy of the shell can be, for example, about 0.1 eV to 3.0 eV, particularly about 0.3 eV to 3.0 eV, more particularly about 0.5 eV to 1.0 eV, higher than the band gap energy of the core. If the difference between the band gap energy of the shell and the band gap energy of the core is small, the proportion of emission other than band edge emission in the emission from the core may increase, and the proportion of band edge emission may decrease.
[0052] Furthermore, the band gap energy of the core and the shell is preferably selected so as to provide a type-I band alignment in which the band gap energy of the shell sandwiches the band gap energy of the core at the heterojunction of the core and the shell. By forming the type-I band alignment, it is possible to obtain better band edge emission from the core. In the type-I alignment, a barrier of at least 0.1 eV is preferably formed between the band gap of the core and the band gap of the shell, and a barrier of 0.2 eV or more, more particularly 0.3 eV or more may be formed. The upper limit of the barrier is, for example, 1.8 eV or less, and particularly 1.1 eV or less. If the barrier is small, the proportion of emission other than the band edge emission in the emission from the core may increase, and the proportion of the band edge emission may decrease.
[0053] The shell may contain Ga as a Group 13 element and S as a Group 16 element. Semiconductors containing Ga and S tend to have larger band gap energies than ternary semiconductors of Group 11-Group 13-Group 16.
[0054] The shell may also be a semiconductor whose crystal system is familiar to that of the core semiconductor. It may also be a semiconductor whose lattice constant is the same as or close to that of the core semiconductor. A shell made of a semiconductor whose crystal system is familiar and whose lattice constant is close (here, a shell whose lattice constant multiple is close to that of the core is also considered to be close) may well cover the periphery of the core. For example, semiconductors of the ternary system of Groups 11-13-16 are generally tetragonal, but examples of familiar crystal systems include tetragonal and orthorhombic. When the Ag-In-Ga-S semiconductor is tetragonal, its lattice constant is 5.828 Å, 5.828 Å, and 11.19 Å, and the shell that covers it is preferably tetragonal or cubic, and its lattice constant or multiple is close to that of the Ag-In-Ga-S semiconductor. Alternatively, the shell may be amorphous.
[0055] Whether or not an amorphous shell is formed can be confirmed by observing the core-shell semiconductor nanoparticles with HAADF-STEM. With HAADF-STEM, substances having a regular structure such as crystalline substances are observed as images having a regular pattern, while substances not having a regular structure such as amorphous substances are not observed as images having a regular pattern. Therefore, when the shell is amorphous, the shell can be observed as a part that is clearly different from the core (which has a crystal structure such as a tetragonal system as described above) that is observed as an image having a regular pattern.
[0056] Furthermore, when the core is made of Ag-In-Ga-S and the shell is made of GaS, the shell tends to be observed as a darker image than the core in the image obtained with HAADF-STEM, because Ga is a lighter element than Ag and In.
[0057] Whether or not an amorphous shell is formed can also be confirmed by observing core-shell semiconductor nanoparticles with a high-resolution transmission electron microscope (HRTEM). In the image obtained with HRTEM, the core portion is observed as a crystal lattice image (an image with a regular pattern), while the shell portion is not observed as a crystal lattice image, and is observed as a portion in which black and white contrast is observed but no regular pattern is visible.
[0058] When the shell is a semiconductor containing Ga and S as a combination of Group 13 and Group 16 elements, the combination of Ga and S can be in the form of gallium sulfide. The gallium sulfide constituting the shell does not have to be of stoichiometric composition (Ga2S3), and in this sense, gallium sulfide is herein referred to as having the formula GaS x (x may be expressed as any number not limited to integers, for example, 0.8 to 1.5).
[0059] Gallium sulfide has a band gap energy of about 2.5 eV to 2.6 eV, and the lattice constant of the tetragonal crystal system is 5.215 Å. However, the crystal systems described here are all reported values, and the shells of actual core-shell semiconductor nanoparticles do not necessarily meet these reported values. Gallium sulfide is preferably used as a semiconductor constituting the shell because it has a larger band gap energy. When the shell is gallium sulfide, stronger band edge emission can be obtained.
[0060] When the shell is a semiconductor containing a combination of Li, Ga, and S as a combination of Group 1, Group 13, and Group 16 elements, it can be in the form of, for example, lithium gallium sulfide. The lithium gallium sulfide does not have to have a stoichiometric composition (for example, LiGaS2), and may have a composition represented by, for example, LiGaSx (x is an arbitrary number not limited to an integer, for example, 1.1 to 2). It may also be in an amorphous form in which Li is dissolved in gallium sulfide. The molar ratio of Li to Ga in the shell (Li / Ga) is, for example, 1 / 20 to 4, or 1 / 10 to 2.
[0061] The band gap energy of lithium gallium sulfide is relatively large at about 4 eV, which allows for stronger band edge emission. In addition, since the ionic radius of Li is equivalent to that of the Ag that forms the core, for example, the shell can have a structure similar to that of the core, compensating for defects on the core surface and thus suppressing defect emission more effectively.
[0062] The shell surface of the core-shell semiconductor nanoparticles may be modified with a surface modifier. Specific examples of the surface modifier include the nitrogen-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms, the sulfur-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms, and the oxygen-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms, as well as compounds containing phosphorus with a negative oxidation number (hereinafter also referred to as "specific modifiers"). When the surface modifier of the shell contains the specific modifier, the quantum yield of the band edge emission of the core-shell semiconductor nanoparticles is improved.
[0063] The specific modifier includes P, which has a negative oxidation number as a Group 15 element. The oxidation number of P is -1 when one hydrogen atom or alkyl group is bonded to P, and +1 when one oxygen atom is bonded to P via a single bond, and changes depending on the substitution state of P. For example, the oxidation number of P in trialkylphosphine and triarylphosphine is -3, and in trialkylphosphine oxide and triarylphosphine oxide, it is -1.
[0064] The specific modifier may contain other Group 15 elements in addition to P having a negative oxidation number. Examples of other Group 15 elements include N, As, and Sb.
[0065] The specific modifying agent may be, for example, a phosphorus-containing compound having a hydrocarbon group having 4 to 20 carbon atoms. Examples of the hydrocarbon group having 4 to 20 carbon atoms include linear or branched saturated aliphatic hydrocarbon groups such as n-butyl, isobutyl, n-pentyl, n-hexyl, octyl, ethylhexyl, decyl, dodecyl, tetradecyl, hexadecyl, and octadecyl groups; linear or branched unsaturated aliphatic hydrocarbon groups such as oleyl; alicyclic hydrocarbon groups such as cyclopentyl and cyclohexyl groups; aromatic hydrocarbon groups such as phenyl and naphthyl groups; and arylalkyl groups such as benzyl and naphthylmethyl groups. Of these, saturated aliphatic hydrocarbon groups and unsaturated aliphatic hydrocarbon groups are preferred. When the specific modifying agent has multiple hydrocarbon groups, they may be the same or different.
[0066] Specific examples of the specific modifying agent include tributylphosphine, triisobutylphosphine, tripentylphosphine, trihexylphosphine, trioctylphosphine, tris(ethylhexyl)phosphine, tridecylphosphine, tridodecylphosphine, tritetradecylphosphine, trihexadecylphosphine, trioctadecylphosphine, triphenylphosphine, tributylphosphine oxide, triisobutylphosphine oxide, tripentylphosphine oxide, trihexylphosphine oxide, trioctylphosphine oxide, tris(ethylhexyl)phosphine oxide, tridecylphosphine oxide, tridodecylphosphine oxide, tritetradecylphosphine oxide, trihexadecylphosphine oxide, trioctadecylphosphine oxide, and triphenylphosphine oxide. At least one selected from the group consisting of these is preferred.
[0067] Method for producing core-shell semiconductor nanoparticles The method for producing core-shell semiconductor nanoparticles includes preparing a dispersion containing semiconductor nanoparticles, adding a semiconductor raw material to the dispersion of semiconductor nanoparticles, and forming a semiconductor layer on the surface of the semiconductor nanoparticles. When coating the semiconductor nanoparticles with a shell, a dispersion is prepared in which the semiconductor nanoparticles are dispersed in an appropriate solvent, and a semiconductor layer that becomes the shell is formed in the dispersion. Since no scattered light occurs in the liquid in which the semiconductor nanoparticles are dispersed, the dispersion is generally obtained as a transparent one (colored or colorless). The solvent for dispersing the semiconductor nanoparticles can be any organic solvent (particularly a highly polar organic solvent such as an alcohol such as ethanol) as in the case of producing the semiconductor nanoparticles, and the organic solvent can be a surface modifier or a solution containing a surface modifier. For example, the organic solvent can be at least one selected from nitrogen-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms, which are surface modifiers described in relation to the method for producing semiconductor nanoparticles, or at least one selected from sulfur-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms, or a combination of at least one selected from nitrogen-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms and at least one selected from sulfur-containing compounds having a hydrocarbon group with 4 to 20 carbon atoms. As the nitrogen-containing compound, n-tetradecylamine, oleylamine, etc. are preferred because they are particularly highly pure and have a boiling point of more than 290°C. As the sulfur-containing compound, dodecanethiol, etc. are preferred. Specific examples of the organic solvent include oleylamine, n-tetradecylamine, dodecanethiol, and combinations thereof.
[0068] The semiconductor nanoparticle dispersion has a particle concentration of, for example, 5.0×10 -7 mol / liter or more 5.0 x 10 -5 moles / liter or less, especially 1.0 x 10 -6 Moles / liter or more: 1.0 x 10 -5If the ratio of particles in the dispersion is too small, it becomes difficult to recover the product by the aggregation and precipitation process in a poor solvent, and if it is too large, the ratio of Ostwald ripening of the material constituting the core and fusion due to collision increases, and the particle size distribution tends to become broader.
[0069] Shell formation The semiconductor layer that becomes the shell is formed, for example, by adding a compound containing a Group 13 element and a simple substance of a Group 16 element or a compound containing a Group 16 element to the above dispersion.
[0070] The compound containing a Group 13 element is a source of the Group 13 element, and is, for example, an organic salt, an inorganic salt, or an organometallic compound of the Group 13 element. Specifically, the compound containing a Group 13 element includes a nitrate, an acetate, a sulfate, a hydrochloride, a sulfonate, and an acetylacetonato complex, and is preferably an organic salt such as an acetate, or an organometallic compound. This is because the organic salt and the organometallic compound have high solubility in an organic solvent, and are likely to cause the reaction to proceed more uniformly.
[0071] A simple substance of a Group 16 element or a compound containing a Group 16 element is a source of the Group 16 element. For example, when sulfur (S) is used as a constituent element of the shell as the Group 16 element, simple sulfur such as high purity sulfur can be used, or a sulfur-containing compound such as thiols such as n-butanethiol, isobutanethiol, n-pentanethiol, n-hexanethiol, octanethiol, decanethiol, dodecanethiol, hexadecanethiol, or octadecanethiol, a disulfide such as dibenzyl sulfide, thiourea, or a thiocarbonyl compound can be used.
[0072] When oxygen (O) is used as the group 16 element for the shell, alcohols, ethers, carboxylic acids, ketones, and N-oxide compounds may be used as the group 16 element source. When selenium (Se) is used as the group 16 element for the shell, simple selenium, selenized phosphine oxide, organic selenium compounds (dibenzyl diselenide and diphenyl diselenide), hydrides, and other compounds may be used as the group 16 element source. When tellurium (Te) is used as the group 16 element for the shell, simple tellurium, tellurized phosphine oxide, and hydrides may be used as the group 16 element source.
[0073] The method of adding the Group 13 element source and the Group 16 element source to the dispersion liquid is not particularly limited. For example, a mixed liquid in which the Group 13 element source and the Group 16 element source are dispersed or dissolved in an organic solvent is prepared, and the mixed liquid may be added to the dispersion liquid little by little, for example, by a method of dropping. In this case, the mixed liquid may be added at a rate of 0.1 mL / hour to 10 mL / hour, particularly 1 mL / hour to 5 mL / hour. The mixed liquid may be added to a heated dispersion liquid. Specifically, for example, the shell layer may be formed by raising the temperature of the dispersion liquid so that its peak temperature is 200°C to 310°C, and after the peak temperature is reached, the mixed liquid is added little by little while maintaining the peak temperature, and then the temperature is lowered (slow injection method). The peak temperature may be maintained as necessary even after the addition of the mixed liquid is completed.
[0074] If the peak temperature is above the above temperature, the surface modifier modifying the semiconductor nanoparticles is sufficiently removed, or the chemical reaction for shell formation proceeds sufficiently, so that the semiconductor layer (shell) tends to be formed sufficiently. If the peak temperature is below the above temperature, the semiconductor nanoparticles are prevented from being altered, and good band edge emission tends to be obtained. The time for holding the peak temperature can be a total of 1 minute to 300 minutes, particularly 10 minutes to 120 minutes, from the start of addition of the mixed liquid. The holding time of the peak temperature is selected in relation to the peak temperature, and if the holding time is longer when the peak temperature is lower, and if the holding time is shorter when the peak temperature is higher, a good shell layer is likely to be formed. The rate of temperature increase and the rate of temperature decrease are not particularly limited, and the temperature decrease may be performed, for example, by holding the peak temperature for a predetermined time, stopping heating by a heating source (e.g., an electric heater), and allowing to cool.
[0075] Alternatively, the Group 13 element source and the Group 16 element source may be added directly in their entirety to the dispersion. Then, the dispersion to which the Group 13 element source and the Group 16 element source have been added may be heated to form a shell semiconductor layer on the surface of the semiconductor nanoparticles (heating-up method). Specifically, the dispersion to which the Group 13 element source and the Group 16 element source have been added may be heated, for example, by gradually increasing the temperature until the peak temperature reaches 200° C. or more and 310° C. or less, and then by gradually decreasing the temperature after maintaining the peak temperature for 1 minute or more and 300 minutes or less. The rate of temperature increase may be, for example, 1° C. / min. or more and 50° C. / min. or less, and the rate of temperature decrease may be, for example, 1° C. / min. or more and 100° C. / min. Alternatively, the temperature increase rate may not be particularly controlled, and the temperature may be heated to a predetermined peak temperature, or the temperature decrease may not be performed at a constant rate, but may be performed by stopping the heating by the heating source and allowing it to cool. The advantage of the peak temperature being within the above range is as explained in the above method of adding a mixed liquid (slow injection method).
[0076] The heating-up method tends to produce core-shell type semiconductor nanoparticles that give stronger band edge emission than when the shell is formed by the slow injection method.
[0077] Regardless of the method of adding the Group 13 element source and the Group 16 element source, the ratio of the two may be determined in accordance with the stoichiometric composition ratio of the compound semiconductor composed of the Group 13 element and the Group 16 element, and may not necessarily be the stoichiometric composition ratio. When the ratio is not the stoichiometric composition ratio, the raw materials may be charged in an amount in excess of the amount of the target shell to be produced, for example, the Group 16 element source may be less than the stoichiometric composition ratio, for example, the ratio may be 1:1 (Group 13:Group 16). For example, when an In source is used as the Group 13 element source and an S source is used as the Group 16 element source, the ratio is preferably 1:1.5 (In:S) to 1:1, which corresponds to the composition formula of In2S3. Similarly, when a Ga source is used as the Group 13 element source and a S source is used as the Group 16 element source, the feed ratio is preferably 1:1.5 (Ga:S) to 1:1, which corresponds to the composition formula of Ga2S3.
[0078] Furthermore, the amounts of the Group 13 element source and the Group 16 element source are selected in consideration of the amount of semiconductor nanoparticles contained in the dispersion so that a shell of the desired thickness is formed on the semiconductor nanoparticles present in the dispersion. For example, the amounts of the Group 13 element source and the Group 16 element source may be determined so that 1 μmol to 10 mmol, particularly 5 μmol to 1 mmol, of a compound semiconductor having a stoichiometric composition consisting of a Group 13 element and a Group 16 element is generated per 10 nmol of substance as particles of the semiconductor nanoparticles. However, the amount of substance as particles is the molar amount when one particle is regarded as a giant molecule, and the number of nanoparticles contained in the dispersion is determined by Avogadro's number (N A =6.022×10 23 ) divided by
[0079] In the method for producing core-shell semiconductor nanoparticles, it is preferable to form a shell containing indium sulfide or gallium sulfide by using indium acetate or gallium acetylacetonate as the Group 13 element source, elemental sulfur, thiourea or dibenzyl disulfide as the Group 16 element source, and a mixture of oleylamine and dodecanethiol as the dispersion liquid.
[0080] In addition, when a mixture of oleylamine and dodecanethiol is used as the dispersion liquid in the heating-up method, core-shell type semiconductor nanoparticles are obtained that give an emission spectrum in which the intensity of the broad peak derived from defect emission is sufficiently smaller than the intensity of the peak of band edge emission. The above tendency is also significantly observed when a gallium source is used as the Group 13 element source.
[0081] In this way, the shell is formed to form the core-shell type semiconductor nanoparticles. The obtained core-shell type semiconductor nanoparticles may be separated from the solvent, and may be further purified and dried as necessary. The methods of separation, purification and drying are as described above in relation to the semiconductor nanoparticles, and therefore detailed description thereof will be omitted here.
[0082] Also, when the semiconductor that becomes the shell is substantially composed of Group 1 elements, Group 13 elements, and Group 16 elements, the shell can be formed in the same manner as above. That is, the shell can be formed by adding a compound containing a Group 1 element, a compound containing a Group 13 element, and a simple substance of a Group 16 element or a compound containing a Group 16 element to a dispersion liquid of semiconductor nanoparticles that become the cores.
[0083] The compound containing a Group 1 element is, for example, an organic salt, an inorganic salt, or an organometallic compound of the Group 1 element. Specific examples of the compound containing a Group 1 element include nitrates, acetates, sulfates, hydrochlorides, sulfonates, and acetylacetonato complexes, and preferably an organic salt such as acetate or an organometallic compound. This is because organic salts and organometallic compounds have high solubility in organic solvents and tend to make the reaction proceed more uniformly.
[0084] When the shell surface of the core-shell semiconductor nanoparticles is modified with a specific modifying agent, the core-shell semiconductor nanoparticles obtained above may be subjected to a modification step. In the modification step, the core-shell semiconductor nanoparticles are contacted with a specific modifying agent containing phosphorus (P) having a negative oxidation number to modify the shell surface of the core-shell particles. This produces semiconductor nanoparticles that exhibit band edge emission with a better quantum yield.
[0085] The contact between the core-shell type semiconductor nanoparticles and the specific modifier can be carried out, for example, by mixing a dispersion of the core-shell type semiconductor nanoparticles with the specific modifier. The core-shell particles may also be mixed with a liquid specific modifier. The specific modifier may be used in its solution. The dispersion of the core-shell type semiconductor nanoparticles can be obtained by mixing the core-shell type semiconductor nanoparticles with a suitable organic solvent. Examples of the organic solvent used for dispersion include halogenated solvents such as chloroform; aromatic hydrocarbon solvents such as toluene; and aliphatic hydrocarbon solvents such as cyclohexane, hexane, pentane, and octane. The concentration of the substance amount in the dispersion of the core-shell type semiconductor nanoparticles is, for example, 1×10 -7 mol / L or more 1×10 -3 mol / L or less, preferably 1×10 -6 mol / L or more 1×10 -4 The amount of substance here is as described in the shell formation section.
[0086] The amount of the specific modifier used relative to the core-shell type semiconductor nanoparticles is, for example, 1 to 50,000 times in terms of molar ratio. -7 mol / L or more 1.0×10 -3 When a dispersion of core-shell type semiconductor nanoparticles having a concentration of mol / L or less is used, the dispersion and the specific modifying agent may be mixed at a volume ratio of 1:1000 to 1000:1.
[0087] The temperature during contact between the core-shell semiconductor nanoparticles and the specific modifying agent is, for example, -100°C to 100°C or -30°C to 75°C. The contact time may be appropriately selected depending on the amount of the specific modifying agent used, the concentration of the dispersion liquid, and the like. The contact time is, for example, 1 minute or more, preferably 1 hour or more, and 100 hours or less, preferably 48 hours or less. The atmosphere during contact is, for example, an inert gas atmosphere such as nitrogen gas or rare gas.
[0088] Light Emitting Device The light-emitting device according to the third embodiment includes a light conversion member containing semiconductor nanoparticles and / or core-shell type semiconductor nanoparticles, and a semiconductor light-emitting element. According to this light-emitting device, for example, a part of the light emitted from the semiconductor light-emitting element is absorbed by the semiconductor nanoparticles and / or core-shell type semiconductor nanoparticles to emit light of a longer wavelength. Then, the light from the semiconductor nanoparticles and / or core-shell type semiconductor nanoparticles and the remaining part of the light emitted from the semiconductor light-emitting element are mixed, and the mixed light can be used as the light emitted by the light-emitting device.
[0089] Specifically, a light-emitting device that emits white light can be obtained by using a semiconductor light-emitting element that emits blue-violet light or blue light with a peak wavelength of about 400 nm or more and 490 nm or less, and semiconductor nanoparticles and / or core-shell type semiconductor nanoparticles that absorb blue light and emit yellow light. Alternatively, a white light-emitting device can be obtained by using two types of semiconductor nanoparticles and / or core-shell type semiconductor nanoparticles, one that absorbs blue light and emits green light, and the other that absorbs blue light and emits red light.
[0090] Alternatively, a white light-emitting device can be obtained by using a semiconductor light-emitting element that emits ultraviolet light with a peak wavelength of 400 nm or less, and three types of semiconductor nanoparticles and / or core-shell type semiconductor nanoparticles that absorb the ultraviolet light and emit blue light, green light, and red light, respectively. In this case, it is desirable to have all the light from the light-emitting element absorbed and converted by the semiconductor nanoparticles and / or core-shell type semiconductor nanoparticles so that the ultraviolet light emitted from the light-emitting element does not leak to the outside.
[0091] The semiconductor nanoparticles and / or core-shell type semiconductor nanoparticles of this embodiment may be used in combination with other semiconductor quantum dots, or may be used in combination with other phosphors that are not semiconductor quantum dots (e.g., organic phosphors or inorganic phosphors). Other semiconductor quantum dots are, for example, binary semiconductor quantum dots described in the Background Art section. As phosphors that are not semiconductor quantum dots, garnet phosphors such as aluminum garnet phosphors can be used. Examples of garnet phosphors include yttrium-aluminum-garnet phosphors activated with cerium and lutetium-aluminum-garnet phosphors activated with cerium. Other examples of the phosphors that are not semiconductor quantum dots include nitrogen-containing calcium aluminosilicate phosphors activated with europium and / or chromium, silicate phosphors activated with europium, β-SiAlON phosphors, nitride phosphors such as CASN or SCASN, rare earth nitride phosphors such as LnSi3N11 or LnSiAlON, BaSi2O2N2:Eu or Ba3Si6O 12 Examples of phosphors that can be used include oxynitride phosphors such as N2:Eu, sulfide phosphors such as CaS, SrGa2S4, SrAl2O4, and ZnS, chlorosilicate phosphors, SrLiAl3N4:Eu phosphors, SrMg3SiN4:Eu phosphors, and K2SiF6:Mn phosphors as manganese-activated fluoride complex phosphors.
[0092] In a light-emitting device, the light conversion member containing semiconductor nanoparticles and / or core-shell type semiconductor nanoparticles may be, for example, a sheet or plate-like member, or may be a member having a three-dimensional shape. An example of a member having a three-dimensional shape is a sealing member formed by filling a resin into a recess formed in a package of a surface-mounted light-emitting diode in order to seal the semiconductor light-emitting element when the semiconductor light-emitting element is disposed on the bottom surface of the recess.
[0093] Another example of the light conversion member is a resin member formed to surround the upper and side surfaces of the semiconductor light emitting element with a substantially uniform thickness when the semiconductor light emitting element is disposed on a planar substrate. Still another example of the light conversion member is a resin member formed in a plate shape with a predetermined thickness on the upper part of the semiconductor light emitting element and the resin member containing the reflector when the semiconductor light emitting element is surrounded by a resin member containing a reflector so that the upper end of the resin member is flush with the semiconductor light emitting element.
[0094] The light conversion member may be in contact with the semiconductor light emitting element, or may be provided away from the semiconductor light emitting element. Specifically, the light conversion member may be a pellet-shaped member, sheet member, plate-shaped member, or rod-shaped member that is provided away from the semiconductor light emitting element, or may be a member provided in contact with the semiconductor light emitting element, such as a sealing member, a coating member (a member that covers the light emitting element provided separately from the molding member), or a molding member (including, for example, a lens-shaped member). In addition, when two or more types of semiconductor nanoparticles or core-shell type semiconductor nanoparticles of the present disclosure that emit light of different wavelengths are used in a light emitting device, the two or more types of semiconductor nanoparticles and / or core-shell type semiconductor nanoparticles of the present disclosure may be mixed in one light conversion member, or two or more light conversion members containing only one type of quantum dot may be used in combination. In this case, the two or more types of light conversion members may form a laminated structure, or may be arranged in a dot-like or stripe-like pattern on a plane.
[0095] The semiconductor light emitting device may be an LED chip. The LED chip may have a semiconductor layer made of one or more kinds selected from the group consisting of GaN, GaAs, InGaN, AlInGaP, GaP, SiC, ZnO, etc. The semiconductor light emitting device that emits blue-violet light, blue light, or ultraviolet light is preferably a semiconductor light emitting device having the general formula In X Al Y Ga 1-X-Y It is preferable that the semiconductor layer is a GaN-based compound represented by N (0≦X, 0≦Y, X+Y<1).
[0096] The light-emitting device is preferably incorporated as a light source in a liquid crystal display device. Since the band-edge emission by the semiconductor nanoparticles and / or core-shell type semiconductor nanoparticles of the present disclosure has a short emission lifetime, a light-emitting device using the same is suitable as a light source for a liquid crystal display device that requires a relatively fast response speed. Furthermore, the semiconductor nanoparticles and / or core-shell type semiconductor nanoparticles of the present disclosure can exhibit an emission peak with a small half-width as the band-edge emission. Therefore, in the light-emitting device: - obtaining blue light having a peak wavelength in the range of 420 nm to 490 nm using the blue semiconductor light-emitting element, and obtaining green light having a peak wavelength in the range of 510 nm to 550 nm, preferably 530 nm to 540 nm, and red light having a peak wavelength in the range of 600 nm to 680 nm, preferably 630 nm to 650 nm, using the semiconductor nanoparticles and / or core-shell type semiconductor nanoparticles of the present disclosure; or In a light-emitting device, the semiconductor light-emitting element is adapted to obtain ultraviolet light having a peak wavelength of 400 nm or less, and the semiconductor nanoparticles and / or core-shell type semiconductor nanoparticles of the present disclosure are adapted to obtain blue light having a peak wavelength of 430 nm or more and 470 nm or less, preferably 440 nm or more and 460 nm or less, green light having a peak wavelength of 510 nm or more and 550 nm or less, preferably 530 nm or more and 540 nm or less, and red light having a peak wavelength of 600 nm or more and 680 nm or less, preferably 630 nm or more and 650 nm or less. As a result, a liquid crystal display device with good color reproducibility can be obtained without using a dark color filter. The light emitting device of the present embodiment is used, for example, as a direct type backlight or an edge type backlight.
[0097] Alternatively, a sheet, plate-like member, or rod made of resin, glass, or the like, containing the semiconductor nanoparticles and / or core-shell type semiconductor nanoparticles of the present disclosure may be incorporated into a liquid crystal display device as a light conversion member independent of the light-emitting device. EXAMPLES
[0098] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0099] Example 1 0.1402 mmol of silver acetate (AgOAc), 0.1875 mmol of indium acetate (In(OAc)3), 0.047 mmol of gallium acetate (Ga(OAc)3) and 0.3744 mmol of thiourea as a sulfur source were added to 0.05 cm 3 of 1-dodecanethiol and 2.95 cm 3 The mixture was poured into a mixed solution of oleylamine and dispersed. The dispersion was placed in a test tube together with a stirrer, and after nitrogen replacement, the contents in the test tube were stirred under a nitrogen atmosphere while performing a heat treatment at 150°C for 10 minutes as the first stage heat treatment and at 250°C for 10 minutes as the second stage heat treatment. After the heat treatment, the obtained suspension was allowed to cool, then centrifuged (radius 146 mm, 4000 rpm, 5 minutes), and the supernatant dispersion was taken out. Methanol was added to this until the semiconductor nanoparticles precipitated, and the mixture was centrifuged (radius 146 mm, 4000 rpm, 5 minutes) to precipitate the semiconductor nanoparticles. The precipitate was taken out and dispersed in chloroform to obtain a semiconductor nanoparticle dispersion. The charged composition of the raw materials is shown in Table 1.
[0100] (Examples 2 and 3) A semiconductor nanoparticle dispersion was obtained in the same manner as in Example 1, except that the composition of the raw materials was changed as shown in Table 1.
[0101] [Table 1]
[0102] Example 4 0.125 mmol of silver acetate (AgOAc), 0.0375 mmol of indium acetylacetonate (In(CH3COCHCOCH3)3; In(AcAc)3), 0.0875 mmol of gallium acetylacetonate (Ga(CH3COCHCOCH3)3; Ga(AcAc)3) and 0.25 mmol of sulfur as a sulfur source were added to 0.25 cm 3 of 1-dodecanethiol and 2.75 cm 3 The dispersion was placed in a test tube together with a stirrer, and the atmosphere was replaced with nitrogen. Then, the contents in the test tube were stirred under a nitrogen atmosphere and heat-treated at 300°C for 10 minutes. After the heat treatment, the semiconductor nanoparticle dispersion was obtained by post-treatment in the same manner as in Example 1. The composition of the raw materials is shown in Table 2.
[0103] (Examples 5 to 8) A semiconductor nanoparticle dispersion was obtained in the same manner as in Example 4, except that the raw material composition and heat treatment conditions were changed as shown in Table 2.
[0104] Example 9 Fabrication of semiconductor nanoparticle cores The raw material composition and heat treatment conditions are shown in Table 2, and heat treatment was carried out in the same manner as above to obtain a semiconductor nanoparticle core dispersion liquid.
[0105] (Examples 10 and 11) Fabrication of core-shell semiconductor nanoparticles Of the dispersion of semiconductor nanoparticle cores obtained in Example 9, the amount of nanoparticles (number of particles) was 1.0 × 10 -5 mmol was weighed out and the solvent was evaporated in a test tube. -5A dispersion was obtained by dispersing 19.3 mg of Ga(acac)3 and 2.75 mg of thiourea in a mixed solvent of 2.75 mL of oleylamine and 0.25 mL of dodecanethiol, and this was stirred at 300 °C for 120 minutes under a nitrogen atmosphere. The mixture was removed from the heating source, cooled to room temperature, and centrifuged (radius 150 mm, 4000 rpm, 5 minutes) to separate the supernatant and precipitate. Methanol was then added to each of the mixture to obtain a precipitate of core-shell type semiconductor nanoparticles, and the solid components were then collected by centrifugation (radius 150 mm, 4000 rpm, 5 minutes). Ethanol was further added and centrifuged in the same manner, and each of the mixtures was dispersed in chloroform and various measurements were performed. Furthermore, when the average particle size of the shell-coated particles was measured, it was 4.3 nm for the core-shell particles obtained from the precipitation and 3.5 nm for the particles obtained from the supernatant, and the difference from the average particle size of the semiconductor nanoparticle cores gave average shell thicknesses of about 0.75 nm and 0.35 nm, respectively. In the following, the core-shell type semiconductor nanoparticle dispersion obtained from the supernatant is referred to as Example 10, and the core-shell type semiconductor nanoparticle dispersion obtained from the precipitation is referred to as Example 11.
[0106] [Table 2]
[0107] Comparative Example 1 Silver acetate (AgOAc) and indium acetate (In(OAc)3) were weighed out so that Ag / Ag+In was 0.3 (Comparative Example 1), 0.4 (Comparative Example 3), and 0.5 (Comparative Example 2), respectively, and the combined amount of the two metal salts was 0.25 mmol. Silver acetate (AgOAc), indium acetate (In(OAc)3), and 0.25 mmol of thiourea were added to 0.10 cm 3 of oleylamine and 2.90 cm 3The suspension was poured into a mixed solution of 1-dodecanethiol and dispersed. The dispersion was placed in a test tube together with a stirrer, and after nitrogen replacement, the contents in the test tube were heated at 150°C for 10 minutes as the first stage of heat treatment while stirring under a nitrogen atmosphere, and then heated at 250°C for 10 minutes as the second stage of heat treatment. After the heat treatment, the resulting suspension was allowed to cool and then centrifuged (radius 146 mm, 4000 rpm, 5 minutes) to precipitate the semiconductor nanoparticles.
[0108] For Comparative Example 1, the obtained precipitate was washed with methanol, and then chloroform was added to the precipitate and centrifuged (radius 146 mm, 4000 rpm, 15 minutes), and the supernatant was collected to obtain a semiconductor nanoparticle dispersion. For Comparative Example 3 and Comparative Example 2, methanol was added to the supernatant dispersion until nanoparticles precipitated, and the mixture was centrifuged (radius 146 mm, 4000 rpm, 5 minutes) to precipitate the semiconductor nanoparticles. The precipitate was taken out and dispersed in chloroform to obtain a semiconductor nanoparticle dispersion.
[0109] (composition analysis) For the obtained semiconductor nanoparticles, a fluorescent X-ray analyzer was used to determine the ratio of each atom when the total number of Ag, In, Ga, and S atoms contained in the semiconductor nanoparticles was taken as 100, and the Ga ratio calculated as Ga / (Ga+In), the Ag ratio calculated as Ag / (Ag+In+Ga), and the S ratio calculated as S / (Ag+In+Ga) were calculated. The results are shown in Table 3.
[0110] (Average particle size) The shape of the obtained semiconductor nanoparticles was observed and the average particle size was measured. The shape of the obtained particles was spherical or polygonal. The average particle size is shown in Table 3.
[0111] (Light Emitting Characteristics) The absorption and emission spectra of the obtained semiconductor nanoparticles were measured. The absorption spectrum was measured using a diode array spectrophotometer (Agilent Technologies, product name Agilent 8453A) with a wavelength of 190 nm to 1100 nm. The emission spectrum was measured using a multichannel spectrometer (Hamamatsu Photonics, product name PMA11) with an excitation wavelength of 365 nm. The emission spectra of Examples 3, 4, 6 and Comparative Example 3 are shown in FIG. 1, and the absorption spectra in FIG. 2. The emission spectra of Examples 10 and 11 are shown in FIG. 4, and the absorption spectra in FIG. 5. The emission peak wavelengths (band edge emission) and half widths of the steep emission peaks observed in each emission spectrum are shown in Table 3. The ratio of the band edge emission intensity to the emission peak intensity of the DAP (donor acceptor pair) transition (Bandedge / DAP) was also determined.
[0112] (X-ray diffraction pattern) The X-ray diffraction (XRD) pattern of the semiconductor nanoparticles obtained in Example 4 was measured and compared with that of tetragonal (chalcopyrite type) AgInS2 and orthorhombic AgInS2. The measured XRD pattern is shown in FIG. 3. From the XRD pattern, it was found that the crystal structure of the semiconductor nanoparticles of Example 4 is almost the same as that of tetragonal AgInS2. The XRD pattern was measured using a powder X-ray diffractometer (trade name SmartLab) manufactured by Rigaku Corporation.
[0113] [Table 3]
[0114] From Table 3, it can be seen that the semiconductor nanoparticles of this embodiment exhibit band edge emission having an emission peak wavelength at a shorter wavelength than that of Comparative Example 3. Furthermore, from the results of Examples 10 and 11, it can be seen that even if the manufacturing method of semiconductor nanoparticles is the same, the smaller the average particle size of the obtained semiconductor nanoparticles is, the shorter the emission wavelength of the band edge emission becomes.
[0115] Example 12 0.0833 mmol of silver acetate (AgOAc), 0.050 mmol of In(acac)3, 0.075 mmol of Ga(acac)3, and 0.229 mmol of sulfur as the sulfur source were added to 0.25 cm 3 of 1-dodecanethiol and 2.75 cm 3 The suspension was placed in a test tube together with a stirrer, and the atmosphere was replaced with nitrogen. Then, the contents in the test tube were stirred under a nitrogen atmosphere and heat-treated at 300°C for 10 minutes. After the heat treatment, the suspension was left to cool, centrifuged (radius 146 mm, 4000 rpm, 5 minutes), and the supernatant dispersion was taken out. Methanol was added to this until the semiconductor nanoparticles precipitated, and the mixture was centrifuged (radius 146 mm, 4000 rpm, 5 minutes) to precipitate the semiconductor nanoparticles. The precipitate was taken out and dispersed in chloroform to obtain a semiconductor nanoparticle dispersion.
[0116] Fabrication of core-shell semiconductor nanoparticles Of the dispersion of semiconductor nanoparticle cores obtained above, the amount of nanoparticles (number of particles) was 1.0 × 10 -5 mmol was weighed out and the solvent was evaporated in a test tube. -5 mol of Ga(acac)3 and 5.33 × 10 -5 mol of thiourea and 2.67 x 10 -5mol of lithium acetate and 3.0 mL of oleylamine were added and dispersed to obtain a dispersion. The molar ratio of Li to Ga in the dispersion (Li / Ga) was 1 / 2. The dispersion was then stirred at 300°C for 15 minutes under a nitrogen atmosphere. The mixture was removed from the heating source, allowed to cool to room temperature, and centrifuged (radius 150 mm, 4000 rpm, 5 minutes) to separate into a supernatant and a precipitate. Methanol was then added to the supernatant to obtain a precipitate of core-shell type semiconductor nanoparticles, and the solid components were then collected by centrifugation (radius 150 mm, 4000 rpm, 5 minutes). Ethanol was further added and centrifuged in the same manner, and each was dispersed in chloroform and various measurements were performed. The average particle size of the particles covered with the shell was measured to be 4.7 nm, and the thickness of the shell was about 0.75 nm on average based on the difference from the average particle size of the semiconductor nanoparticle core.
[0117] The composition analysis and emission spectrum measurement of the obtained core-shell type semiconductor nanoparticles were carried out in the same manner as described above. The results are shown in Table 4. The emission spectrum is shown in FIG.
[0118] (Examples 13 to 16) Ga(acac)3 and thiourea in an amount of 5.33 × 10 -5 Core-shell type semiconductor nanoparticles were prepared in the same manner as in Example 12, except that the molar ratio of Li to Ga in the dispersion (Li / Ga) was fixed at 100 mol and the amount of lithium acetate added was changed as shown in the table below. The results are shown in Table 4. The emission spectrum is shown in FIG.
[0119] (Examples 17 to 18) The amount of lithium acetate and thiourea is 5.33 x 10 -5 Core-shell semiconductor nanoparticles were prepared in the same manner as in Example 12, except that the molar ratio of Li to Ga in the dispersion (Li / Ga) was fixed at 1.0 mol and the amount of Ga(acac)3 added was changed as shown in the table below. The results are shown in Table 4. The emission spectrum is shown in Figure 7.
[0120] [Table 4]
[0121] When the shell contains Li, a group 1 element, the defect emission DAP emission is reduced and the intensity of the band-edge emission is improved. When the amount of Li is more than that of Ga, the emission wavelength of the band-edge emission shifts to shorter wavelengths.
[0122] (Example 19) Trioctylphosphine (TOP) was added in an approximately equal volume to the dispersion of the core-shell semiconductor nanoparticles obtained in Example 12 under a nitrogen atmosphere. After shaking and mixing at room temperature for 10 minutes, the mixture was allowed to stand at room temperature for 20 hours in the dark to obtain a dispersion of TOP-modified core-shell semiconductor nanoparticles.
[0123] The emission spectrum and internal quantum yield of the obtained TOP-modified core-shell semiconductor nanoparticles were measured in the same manner as described above. The internal quantum yield of the core-shell semiconductor nanoparticles was 13.5%, while the internal quantum yield of the TOP-modified core-shell semiconductor nanoparticles was 31.4%. The emission spectrum is shown in Figure 8.
Claims
1. Contains Ag, In, Ga and S and has a chalcopyrite crystal structure; A semiconductor nanoparticle which, when irradiated with light, emits light having an emission peak wavelength in the range of 500 nm or more and less than 590 nm, and has an exciton peak observed in the range of 450 nm or more and less than 590 nm in its absorption spectrum.
2. a ratio of the number of Ag atoms to the total number of Ag, In, and Ga atoms is 0.05 or more and 0.55 or less, 2. The semiconductor nanoparticle according to claim 1, having a composition in which the ratio of the number of Ga atoms to the total number of In and Ga atoms is 0.2 or more and 0.9 or less.
3. a ratio of the number of Ag atoms to the total number of Ag, In, and Ga atoms is 0.3 or more and 0.55 or less, 2. The semiconductor nanoparticle according to claim 1, having a composition in which the ratio of the number of Ga atoms to the total number of In and Ga atoms is 0.5 or more and 0.9 or less.
4. a ratio of the number of Ag atoms to the total number of Ag, In, and Ga atoms is 0.05 or more and 0.27 or less, 2. The semiconductor nanoparticle according to claim 1, having a composition in which the ratio of the number of Ga atoms to the total number of In and Ga atoms is 0.25 or more and 0.75 or less.
5. The semiconductor nanoparticles according to any one of claims 1 to 4, and a semiconductor material having a band gap energy greater than that of the semiconductor nanoparticles.
6. The semiconductor nanoparticle of claim 5 , wherein the semiconductor material comprises a Group 13 element and a Group 16 element.
7. The semiconductor nanoparticles according to claim 6 , wherein the semiconductor material contains at least Ga as the Group 13 element.
8. The semiconductor nanoparticles according to claim 6 or 7, wherein the semiconductor material contains at least S as the Group 16 element.
9. A light conversion member comprising the semiconductor nanoparticles according to claim 1 .
10. The light conversion member according to claim 9 , further comprising at least one kind selected from the group consisting of semiconductor nanoparticles other than the semiconductor nanoparticles, an organic phosphor, and an inorganic phosphor.
11. The light conversion member according to claim 9 or 10, which is a sheet-like member or a plate-like member.
12. The light conversion member according to any one of claims 9 to 11, A light emitting device comprising: a semiconductor light emitting element having an emission peak wavelength of 400 nm or more and 490 nm or less.
13. A liquid crystal display comprising the light emitting device according to claim 12.
Citation Information
Patent Citations
Preparation method of core-shell structure quantum dot
CN102212363A
Phosphor and method for manufacturing the same
JP2007169605A
Copper-indium-gallium-chalcogenide nanoparticle precursor for thin-film solar cells
JP2016521232A
Semiconductor nanoparticle and manufacturing method therefor
JP2017025201A
Core-shell type nanoparticles for a photo-electric power absorption layer
JP2017501571A